The Oils from Stems, Leaves and Roots of Elephantopus scaber Linn. - Zailani, Mohd Alhafiizh; Badruddin Ahmad, Fasihuddin (Borneo Journal of Resource Science and Technology, 2016)
The oil from stems, leaves and roots of Elephantopus scaber Linn. were extracted by solvent maceration technique. The percentage yield oil from stems, leaves and roots are 0.001%, 0.003% and 0.04%, respectively. The stem oil gives major constituents of pentacosane (12.3%), lupenyl acetate (11.7%) and fern-7-en-3β-ol (11.0%), while the leaf oil contains isooctyl phthalate (19.2%), hexadecanoic acid (15.0%) and α-linolenic acid (5.0%) as the major components. The major constituents identified in the root oil are hemellitol (11.6%), octyl phthalate (6.0%), 1-nonadecanol (5.6%) and 1-octadecanol (5.5%). There were only three compounds detected and identified in all three parts of the plant, namely decanedioic acid, bis-(2-ethylhexyl)ester, dotriacontane and pentacosane. The oils were analysed by gas chromatography-mass spectrometer and the compounds were identified by comparison with the mass spectral fragmentation pattern database.